The Impact of Reaction Parameters on Graphene-like Material Synthesized using Chemical Vapour Deposition - Khor, C. S. (2017)
The remarkable properties of graphene have directly accelerated the graphene research. Due to its unique and remarkable characteristics, graphene can be potentially used in various applications.